Perubahan Bunyi pada proses Pembentukan Nomina Majemuk Bahasa Jepang - Wahyuni, Sri (Universitas Andalas, 2024)
This article explains the sound changes when two nouns combine to form a compound noun in Japanese and describes the change process. The research data consists of oral data from several NHK Word Premium television programs. Data was collected using observation methods such as basic tapping techniques, advanced techniques, free-hand techniques, and note-taking. The obtained data were cross-referenced with the Japanese-Indonesian Modern Kanji Dictionary to find written equivalents. The data was then analyzed according to the theoretical basis of the research. Data analysis was carried out using methods such as the agih method and direct constituent segmentation techniques to divide the linguistic units of nouns from compound nouns. The discussion concluded that word formation in combining two or more nouns to form a compound noun in Japanese causes a change in the initial consonant sound in the second noun. There are eight changes in the sound of the initial consonant in the second noun when two or more nouns combine to form a compound noun. The initial consonants of the second noun that undergo the change process were [ k ], [ s ], [ t ] [ ç], [ h ], [ f ], [ Ɵ ], and [ ʃ]. While the occurred changes were: [k] → [g], [s] → [z], [t] → [d], [ç] → [ ɟ ], [h] → [b], [f] → [b], [Ɵ] → [z], dan [ ʃ ] → [ ɟ ]. The sound changes occur when two nouns are combined to form a compound noun. Some changes result in similar or adjacent sounds, while others do not. However, all changes involve switching from voiceless sounds to voiced sounds. These sound changes are based on Japanese syllable patterns found in the list of hiragana letters.